Lokalne konteksty globalnych utworów. Ku „autentyczności” muzyki popularnej z miejskiej perspektywy - Kopaniecki, Jakub (Res Facta Nova, 2025)
Value terms such as ‘authentic’ are among the most overloaded in musical discourse. This is well evident in the study of popular music, strongly linked to commercial processes around the world. It is therefore worth changing the perspective to a much narrower, local one and looking at the practices of urban musical communities. For it is among amateur musicians, that the question of musical authenticity plays a defining role. For many of them, music is a kind of engaging leisure practice that determines their identity. This in turn implies the question of the relationship between the sonic identity of the city and the identity of the individual, what is authentic to the city and what is authentic to the subject. The relationship of popular music to people, places and the city as a whole needs to be explored in order to come closer to understanding one dimension of ‘authenticity’ - what it might be in the ‘micro’ scope.